VD_FINDINFO HC / 2010 / 505 vom 30. Juli 2010 - VD Tribunal cantonal (2010)
DIVORCE SUR DEMANDE UNILATÉRALE, AUTORITÉ PARENTALE, DROIT DE GARDE, CURATELLE ÉDUCATIVE | 133 CC, 145 al. 2 CC, 308 CC, 444 CPC, 445 CPC, 451 ch. 2 CPC